Control strategies with human factors for active steering - Hellewell, Joseph S. (2020)
Autonomous road vehicles are an increasingly popular research topic due to their potential to reduce the number of road deaths and road accidents while increasing energy efficiency of the vehicle and reducing congestion. To ensure a successful implementation of driverless cars, it is necessary that the vehicle's behaviour is acceptable to its occupants; that they feel as safe and comfortable as reasonably possible. What the resulting behaviour and driving style is like is different for different people and so it is necessary that an autonomous vehicle can change its performance accordingly.